Employee Performance Is Assessed in Terms of Competence, Motivation, Discipline and Work Environment - Faradila Rochimah; Sarsono Sarsono; Sudarwati Sudarwati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The objectives of this study are to examine and analyze: The effect of competency on the performance of employees at KPP Pratama Surakarta, The effect of motivation on the performance of employees at KPP Pratama Surakarta, The effect of work discipline on the performance of employees at KPP Pratama Surakarta, and The effect of the work environment on the performance of employees at KPP Pratama Surakarta. The author uses a quantitative approach in this research. The population and sample for this study are all employees at the KPP Pratama Surakarta, totaling 101 employees. The sampling technique used is saturated sampling or census, where all members of the population are included as the sample. The data analysis technique used is multiple linear regression analysis. Based on the results of the study, it can be concluded that: Competence affects employee performance at KPP Pratama Surakarta, Work motivation affects employee performance at KPP Pratama Surakarta, Work discipline affects employee performance at KPP Pratama Surakarta, and The work environment affects employee performance at KPP Pratama Surakarta.